The problem of islamophobia and its consequences as obstacles to peacebuilding in Bosnia and Herzegovina - Zalta, Anja (Annales. Series historia et sociologia, 2020)
The article focuses on the question of Islamophobia or "Turkophobia" in specific historical contexts and dynamics in Bosnia and Herzegovina. The article discusses the definition of Islamophobia in combination with the Eurocentric compression of racism that can be recognized in Orientalist discourses. It also emphasizes that Islamophobia and/as Muslim hatred in the south Slavic area has deep historic roots. An in-depth understanding of the special socio- cultural, historical, political and religious characteristics of Bosnia and Herzegovina is a precondition for imagining possibilities of ensuring peace and for consistent application of new models and methods for peacebuilding and peaceful coexistence.
Keywords: Bosna in Hercegovina; islamofobija; medreligijski dialog; neootomanizem; orientalizem; rasizem; Turčuja; turkofobija